Socio-economic Impact Evaluation of Cooperative-Based Melon Picking Agrotourism in Kebon Ayu Village - Zainab Zainab; Jalaludin (Journal of Biology, Environment, and Edu-Tourism, 2025)
Agrotourism has become a strategic approach to rural development by enhancing the socio-economic conditions of farming communities. This study evaluates the socio-economic impact of the "Petik Melon" agrotourism initiative, managed through a cooperative model in Kebon Ayu Village, West Lombok. The research aims to assess the effectiveness and sustainability of this model in improving community welfare. Using a mixed-methods approach and the Analytical Hierarchy Process (AHP), data were gathered through interviews, focus group discussions, and questionnaires involving cooperative members, farmers, visitors, and village officials. The AHP method helped prioritize key indicators such as income generation, employment, social cohesion, and community participation. Findings show that the initiative significantly increased household income, created jobs, and strengthened social bonds. "Income improvement" and "community participation" were identified as the most impactful indicators. Despite these benefits, challenges remain in infrastructure and cooperative capacity. The study concludes that the "Petik Melon" model offers a replicable and impactful strategy for rural development. It recommends enhanced institutional support, improved marketing, and integration of educational-tourism elements to ensure long-term sustainability.